Serum zinc deficiency could be associated with dementia conversion in Parkinson’s disease - Lee, Jieun; Park, Suyeon; Jang, Wooyoung (Frontiers in Aging Neuroscience, 2023)
Background: Association between heavy metals and Parkinson’s disease (PD) is well noted, but studies regarding heavy metal levels and non-motor symptoms of PD, such as PD’s dementia (PD-D), are lacking. Methods: In this retrospective cohort study, we compared five serum heavy metal levels (Zn, Cu, Pb, Hg, and Mn) of newly diagnosed PD patients (n = 124). Among 124 patients, 40 patients were later converted to Parkinson’s disease dementia(PD-D), and 84 patients remained without dementia during the follow-up time. We collected clinical parameters of PD and conducted correlation analysis with heavy metal levels. PD-D conversion time was defined as the initiation time of cholinesterase inhibitors. Cox proportional hazard models were used to identify factors associated with dementia conversion in PD subjects. Results: Zn deficiency was significant in the PD-D group than in the PD without dementia group(87.53 ± 13.20 versus 74.91 ± 14.43, p<0.01). Lower serum Zn level was significantly correlated with K-MMSE and LEDD at three months(r = -0.28, p < 0.01; r = 0.38, p < 0.01). Zn deficiency also contributed to a shorter time to dementia conversion(HR 0.953, 95% CI 0.919 to 0.988, p<0.01). Conclusions: This clinical study suggests that a low serum Zn level can be a risk factor for developing PD-D and could be used as a biological marker for PD-D conversion.